2015
DOI: 10.5558/tfc2015-024
|View full text |Cite
|
Sign up to set email alerts
|

Understanding First Nations rights and perspectives on the use of herbicides in forestry: A case study from northeastern Ontario

Abstract: This article provides forestry professionals with an improved understanding of why First Nations are opposed to the use of chemical herbicides for silvicultural purposes on their traditional lands, based on a case study in northeastern Ontario. Results were generated using a modified form of a focus group approach. First Nations opposition to herbicide use involved not only concerns over human and environmental health (concerns common among the general public) but also spanned from treaty rights, mistrust, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For example, many IPs are limiting local levels of N pollution through the maintenance of traditional agricultural practices with minimal use of chemical pesticides or fertilizers (Wezel et al 2014). Organic farming is an integral part of many IPs' food production systems, including the Maya of Mexico and the Wanka of Peru (Grossman 2003; Moreno‐Peñaranda and Egelyng 2008; Huaman 2014), in which applying natural pest control is more congruent with traditional IPs' worldviews than the use of modern pesticides and agrotoxics (Kayahara and Armstrong 2015; Malmer and Tengö 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For example, many IPs are limiting local levels of N pollution through the maintenance of traditional agricultural practices with minimal use of chemical pesticides or fertilizers (Wezel et al 2014). Organic farming is an integral part of many IPs' food production systems, including the Maya of Mexico and the Wanka of Peru (Grossman 2003; Moreno‐Peñaranda and Egelyng 2008; Huaman 2014), in which applying natural pest control is more congruent with traditional IPs' worldviews than the use of modern pesticides and agrotoxics (Kayahara and Armstrong 2015; Malmer and Tengö 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This was historically done by recurrent surface fires that have mostly been eliminated by fire suppression policies in several jurisdictions including Quebec. Site preparation can be done mechanically, with chemicals or prescribed burning (e.g., [51]), the latter two methods being prohibited in Quebec (but see [63] for a thorough discussion of the acceptability of such practices in Indigenous contexts). If natural regeneration is the selected strategy for white pine establishment, site preparation must coincide with the occurrence of mast seed years to maximize stocking.…”
Section: Site Preparationmentioning
confidence: 99%
“…Additionally, in studying how participants perceived each other's values, it was demonstrated that perceptions are often based on stereotypical views of particular groups, which do not often reflect the true views held by individuals within that group (Lee and Kant 2006). In light of these insights, it becomes clear that groups must work to build strong relationships and use them to develop management strategies that meet the objectives of all parties, rather than imposing systems and practices that the dominant group finds acceptable and expedient (Kayahara and Armstrong 2015). Using the example of vegetation management, Wyatt et al (2011b) reinforce this notion by asserting that, since no universal Indigenous perspective exists, forest managers must consider how their values and perceptions compare to the broader public's and begin to work more collaboratively with communities to develop mutually-acceptable strategies that meet each party's objectives and concerns.…”
Section: Building Respectful Relationshipsmentioning
confidence: 99%